Desert hedgehog mediates the proliferation of medaka spermatogonia through Smoothened signaling. Issue 4 (24th February 2022) - Zhao, Changle; Zhang, Zeming; Qu, Ximei; Bai, Xiaoming; Liu, Xingyong; Tao, Wenjing; Zhou, Linyan; Wang, Deshou; Wei, Jing
Abstract : Desert hedgehog (DHH) signaling has been reported to be involved in spermatogenesis and the self-renewal of spermatogonial stem cells (SSCs). However, the role of DHH in proliferation of spermatogonia including SSCs remains to be elucidated. Here, we report that Dhh from medaka ( Oryizas latipes ) (named as OlDhh) could directly mediate the proliferation of spermatogonia via Smoothened (Smo) signaling. Oldhh is 1362 bp in length and encodes 453 amino acid (aa) residues with more than 50% identity with the homologs in other species. It has expression predominantly restricted to testis. The soluble and tag-free 176-aa mature OlDhh (named as mOlDhh) were successfully obtained by fusing with the N-terminal tag of cleavable 6-histidine and small ubiquitin-related modifier and then removing the tag. Notably, mOlDhh significantly promoted the proliferation of SG3 (a spermatogonial stem cell line from medaka testis) in a dose-dependent manner and spermatogonia in testicular organ culture. Furthermore, the proliferation of SG3 in the presence of mOlDhh could be inhibited by Smo antagonist (cyclopamine) resulting in apoptosis. Additionally, mOlDhh significantly upregulated the expression of smo as well as the pluripotent-related genes bcl6b and sall4 . These data suggest that Smo is an indispensable downstream component in the Dhh signaling pathway. In conclusion, our findings unambiguously demonstrate that Dhh could directly mediate the proliferation of spermatogonia through Smo signaling. This study provides new knowledge about the proliferation regulation of spermatogonia.